Effects of Short-term Hyper- and Hypoprolactinaemia on Hormones of the Pituitary, Gonad and -Thyroid Axis and on Semen Quality in Male Beagles - Koivisto, M. B. [UNESP]; Eschricht, F.; Urhausen, C.; Hoppen, H. O.; Beyerbach, M.; Oei, C. H. Y.; Guenzel-Apel, A. R. (Wiley-Blackwell Publishing, Inc, 2009)
Effects of a short-term hyper- and hypoprolactinaemia on serum concentrations of LH, testosterone and semen quality in six male Beagles were investigated. Blood samples were collected at 3-day intervals for 12 weeks. The time span was divided into five 3-week periods: pre-treatment, metoclopramide (MCP) treatment (0.2 mg/kg orally three times daily), cabergoline (CAB) treatment (5 mu g/kg orally once daily), post-treatment 1 and post-treatment 2. In the latter, only semen characteristics were evaluated. Semen parameters were analyzed once per week during the whole 15-week investigation time. At the end of each period, the effects of a single intravenous injection of thyrotropin-releasing hormone (TRH; 10 mu g/kg) on the secretion of prolactin (PRL), LH, testosterone, thyroid-stimulating hormone and thyroxine (T4) were investigated. Pre-treatment serum PRL concentration increased under MCP (p < 0.05), followed by a decrease under CAB administration (p < 0.05). Luteinizing hormone and testosterone concentrations were not affected. Except for straight-line sperm velocity, semen quality did not differ between collection periods. A single iv TRH injection induced a significant PRL increase at 20 min in all experimental periods except during CAB treatment. Luteinizing hormone and testosterone did not show clear TRH-related changes. Basic T4 levels were significantly reduced after CAB treatment ( p < 0.05). The results of the present study demonstrate that MCP-induced short-term hyperprolactinaemia in male beagles does not seriously affect the hypothalamo-pituitary axis and semen quality.